(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2024)
The article reveals the peculiarities of the functioning of the domestic banking system and examines the latest innovative solutions in the banking sector of the leading countries of the world for the period from 2020 to 2024. The prerequisites for the most popular innovative solutions and ideas in the context of the COVID-19 pandemic are revealed. The author analyzes the situations that have contributed to instability, including the constant interference of cybercriminals and Russia’s military actions against Ukraine. The author systematizes the main directions of development of innovations in the global banking sector and analyzes the possibilities of implementing the most promising ones in the functioning of Ukrainian banking institutions and ensuring their financial security. The author presents the signs and criteria of innovation and provides examples of an innovative approach to solving issues in the internal processes of banking activities. It is determined that the main features of banking innovations are: the presence of social and economic results, reduction of banking costs, reduction of banking risks, increase in the level of liquidity of banking institutions, the presence of unique consumer properties, globalization of banking institutions and increase in labor productivity in the banking sector. The author studies the trends of transformations in the digital component of the banking sector. Innovations in customer experience and marketing innovations in the global banking sector are analyzed. The main directions of development of the banking sector in the context of leading banking institutions are structured, direct ideas and solutions to modern economic challenges of both global and local scales are presented. Innovations in the internal processes of banking institutions in 2020-2023 in Poland, the USA and Spain are revealed.